2004
DOI: 10.1007/s00425-004-1207-8
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate activates cation currents in the plasma membrane of Arabidopsis root cells

Abstract: The effect of glutamate on plant plasma membrane cation transport was studied in roots of Arabidopsis thaliana (L.) Heynh. Patch-clamp experiments using root protoplasts, (22)Na(+) unidirectional fluxes into intact roots and measurements of cytosolic Ca(2+) activity using plants expressing cytosolically-targeted aequorin in specific cell types were carried out. It was demonstrated that low-millimolar concentrations of glutamate activate within seconds both Na(+) and Ca(2+) currents in patch-clamped protoplasts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
69
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 98 publications
(72 citation statements)
references
References 32 publications
3
69
0
Order By: Relevance
“…The measurements were performed in the luminometer cuvette (2 mL) containing coelenterazine (1 mM)-free base. The reading began after giving a 20-s blue light (20 mmol/ m 2 /s) pulse in the luminometer (FG-200) (Wang and Gu, 1986;Demidchik et al, 2004;Hu et al, 2004;Love et al, 2004). Fluorescence was generated by the sum of autofluorescence of chlorophyll and aequorin luminescence.…”
Section: Measurement Of [Ca 21 ] Cytmentioning
confidence: 99%
“…The measurements were performed in the luminometer cuvette (2 mL) containing coelenterazine (1 mM)-free base. The reading began after giving a 20-s blue light (20 mmol/ m 2 /s) pulse in the luminometer (FG-200) (Wang and Gu, 1986;Demidchik et al, 2004;Hu et al, 2004;Love et al, 2004). Fluorescence was generated by the sum of autofluorescence of chlorophyll and aequorin luminescence.…”
Section: Measurement Of [Ca 21 ] Cytmentioning
confidence: 99%
“…The last category relates closely to the presumed molecular function of GLRs because the homologous ionotropic Glu receptors (iGluRs) in animals combine as heterotetramers to form amino acid-gated ion channels with varying permeability to Na + , K + , and Ca 2+ (Traynelis et al, 2010). That plant GLRs encode similar ion transporting functions was a logical initial hypothesis, one that was suggested to account for the prevalence of nonselective cation currents across plant cell membranes (Stoeckel and Takeda, 1989;Demidchik et al, 2002Demidchik et al, , 2004White et al, 2002) and promised to add some much-needed molecular detail to the mechanism of how cytoplasmic Ca 2+ signals are generated (Sanders et al, 2002;Kudla et al, 2010). The case was strengthened by the finding that the large, transient membrane depolarization and rise in cytoplasmic Ca 2+ triggered by a defined set of amino acids in wild-type plants depended on GLR genes (Dennison and Spalding, 2000;Qi et al, 2006;Stephens et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The rise in Ca 21 triggered by Glu is accompanied by a large, transient membrane depolarization that is due at least in part to Ca 21 influx across the plasma membrane (Dennison and Spalding, 2000;Meyerhoff et al, 2005). A patch-clamp study concluded that Glu activated nonspecific cation channels in root cells, which may be the conductances responsible for these ionic responses (Demidchik et al, 2004). Overexpression of GLR3.2 led to poor plant health that was ameliorated by treatment with Ca 21 , and to hypersensitivity to K 1 and Na 1 (Kim et al, 2001).…”
mentioning
confidence: 99%